2019
DOI: 10.1088/1475-7516/2019/10/062
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational wave signatures from an extended inert doublet dark matter model

Abstract: We consider a particle dark matter model by extending the scalar sector of the Standard Model by an additional SU(2) scalar doublet which is made "inert" (and stable) by imposing a discrete Z 2 symmetry under which the additional scalar doublet is odd (and the SM is even) and it does not develop any vacuum expectation value (VEV). The lightest inert particle (LIP) of this inert doublet model (IDM) can be a viable candidate for Dark Matter. The IDM model is further extended by an additional singlet scalar which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 120 publications
0
15
0
Order By: Relevance
“…Although the first-order electroweak (EW) phase transition (PT) would have been possible in the framework of SM of particle physics through the Higgs mechanism but with the observed Higgs mass of 125.09 GeV [34][35][36][37] the transition is a smooth cross-over and not a first-order one. However, in literature there are ample references where the authors have shown that SFOPT can be realised by simple extension of SM [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. In the present work however, we primarily explore GW emission from the annihilation of domain walls by proposing a simple extension of SM with two complex scalars.…”
Section: Jhep05(2021)223mentioning
confidence: 99%
See 2 more Smart Citations
“…Although the first-order electroweak (EW) phase transition (PT) would have been possible in the framework of SM of particle physics through the Higgs mechanism but with the observed Higgs mass of 125.09 GeV [34][35][36][37] the transition is a smooth cross-over and not a first-order one. However, in literature there are ample references where the authors have shown that SFOPT can be realised by simple extension of SM [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. In the present work however, we primarily explore GW emission from the annihilation of domain walls by proposing a simple extension of SM with two complex scalars.…”
Section: Jhep05(2021)223mentioning
confidence: 99%
“…In refs. [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] the authors have proposed different particle physics models for the production of GWs from first-order phase transition but variance from their approaches in this work, we consider an extension of SM with two complex scalars in such a way that it can provide GW production from SFOPT as well as the GW production from unstable domain walls. We constrain the model parameters by using some theoretical and experimental constraints such as vacuum stability, perturbativity and the collider bounds.…”
Section: Jhep05(2021)223mentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in the Sec. I, GWs are produced from the FOPT majorly via three mechanisms namely, bubble collisions [66][67][68][69][70][71][72], sound wave [73][74][75][76] and turbulence in the plasma [77][78][79][80][81]. The total GW intensity Ω GW h 2 as a function of frequency can be expressed as the sum of the contributions from the individual components [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81]:…”
Section: B Gravitational Wave From Sfoptmentioning
confidence: 99%
“…The production of GW spectrum happens mainly via three processes: bubble collisions [66][67][68][69][70][71][72], sound wave [73][74][75][76] and turbulence in the plasma [77][78][79][80][81]. The signal thus produced can be detected in different GW detectors, for example, space-based detectors like Advanced Laser Interferometer Antenna (ALIA) [82], Big Bang Observer(BBO) [83], Deci-hertz Interferometer Gravitational wave Observatory (DECIGO) [84], Laser Interferometer Space Antenna(LISA) [85], groundbased detector advanced Laser Interferometer Gravitational-Wave Observatory (aLIGO) [86] etc.…”
Section: Introductionmentioning
confidence: 99%